2021
DOI: 10.1016/j.hlc.2020.05.112
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Versus Surgical Aortic Valve Replacement: An Updated Systematic Review and Meta-Analysis With a Focus on Outcomes by Sex

Abstract: Background and Aims Women at increased surgical risk have been shown to have better outcomes with transcatheter aortic valve implantation (TAVI) as compared to surgical valve replacement (SAVR). With the scope of TAVI moving into low-surgical risk patients, we aimed to update the current literature to include the new low-risk randomised controlled trial (RCT) data in investigating outcomes by sex. Methods We systematically searched MEDLINE (Ovid), PubMed, Cochrane Central Register of Controlled Trials (CENTRAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
4
0
1
Order By: Relevance
“…Moreover, it has been demonstrated that women present a significant improvement of LVEF after TAVR [ 20 ], which may account for superior survival. Our 1-year death rate (11.5%) is in line with that reported by PARTNER II trial (12.3%), confirmed by a recent meta-analysis [ 2 , 21 ]. Women of our cohort have been associated with better survival also at 3-year, as similarly reported in a recent publication [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it has been demonstrated that women present a significant improvement of LVEF after TAVR [ 20 ], which may account for superior survival. Our 1-year death rate (11.5%) is in line with that reported by PARTNER II trial (12.3%), confirmed by a recent meta-analysis [ 2 , 21 ]. Women of our cohort have been associated with better survival also at 3-year, as similarly reported in a recent publication [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were observed at 2-year follow-up. The findings have been confirmed by a more recent meta-analysis by Dagan et al [23], and this reflects the increased operative risk of women undergoing cardiac surgery [24]. Previous studies did not document a clear benefit of TAVR in terms of survival in high-risk patients, but there is a lack of specific data in patients treated with new-generation devices.…”
Section: Discussionmentioning
confidence: 63%
“…Duas metanálises compararam as diferenças de sexo nos desfechos de TAVR e SAVR, com níveis de confiança moderados na escala AMSTAR-2 ( Tabela Suplementar 3 ). 19 , 20 Os estudos identificaram que o TAVR em mulheres estava associado a uma redução no risco de morte e IRA, mas não em homens. No entanto, o TAVR aumentou significativamente o risco de IMD em homens, mas não em mulheres.…”
Section: Outros Grupos Populacionais: Visão Geral Das Revisões Sistem...unclassified